2011
DOI: 10.31357/jtfe.v1i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Neem Leaf Extracts (Azadirachta indica A. Juss) on Some Haematological, Ionoregulatory, Biochemical and Enzymological Parameters of Indian Major Carp, Cirrhinus mrigala

Abstract: In the present study, the median lethal concentration (LC 50) of neem leaf extract to Cirrhinus mrigala for 24 h was found to be 1.035 g l -l . During the study period, the haematological parameters including Hb, Hct, RBC, MCV, MCH and MCHC levels were significantly decreased in neem leaf extract exposed fish when compared to the control fish whereas WBC count was increased. Similarly, plasma Na + and Cllevels were significantly lower and K + level were significantly higher when compared to the control. In bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
7
16
3
Order By: Relevance
“…Acute toxicity of neem based biopesticides, Nimbecidine (EC-Azadirachrtin 0.03%) and Neem Gold (EC-Azadirachtin A 0.15%) for the fingerlings of a freshwater loach, Lepidocephalichthys guntea were determined by Mondal et al (2007) (Shoba et al, 2010) and the 96hr LC50 value was observed to be 0.0028 ppm. In another toxicity studies, the 24hr LC50 values of neem leaves extract to the Indian major carps, Cirrhinus mrigala and Labeo rohita were found to be 1.035 g L -l (Saravanan et al, 2010(Saravanan et al, , 2011. Similarly, Kumar et al (2012) for 96 hr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute toxicity of neem based biopesticides, Nimbecidine (EC-Azadirachrtin 0.03%) and Neem Gold (EC-Azadirachtin A 0.15%) for the fingerlings of a freshwater loach, Lepidocephalichthys guntea were determined by Mondal et al (2007) (Shoba et al, 2010) and the 96hr LC50 value was observed to be 0.0028 ppm. In another toxicity studies, the 24hr LC50 values of neem leaves extract to the Indian major carps, Cirrhinus mrigala and Labeo rohita were found to be 1.035 g L -l (Saravanan et al, 2010(Saravanan et al, , 2011. Similarly, Kumar et al (2012) for 96 hr.…”
Section: Resultsmentioning
confidence: 99%
“…al., 1996;Mahboob et al, 1998). The adverse effects of neem based biopesticides on the non-target organisms due to indiscriminate usage were also reported (Schmutterer and Holst 1987;Beckage et al 1988;Price and Schuster 1991;Schöder, 1992;Okpanachi, 1992, 1997;Winkaler et al, 2007;Saravanan et al, 2010Saravanan et al, , 2011Maitra et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…2.5.7 besides its extensive use in fish farms to control fish parasites and fish fry predator insects [8][9] . Its piscicidal potential is embedded in the alkaloids that may cause functional changes in biochemical activities and organ morphology of the fish species 3,[5][6][10][11] . Therefore, the objective of the present study was to determine the acute toxicity of neem leaf extract to the snake headed fish, Channa gachua (Ham.)…”
Section: Doimentioning
confidence: 99%
“…It has also been suggested as an alternative phyto-piscicide by some earlier workers [3][4][5][6][7] Access this article online Quick Response Code:…”
Section: Introductionmentioning
confidence: 99%
“…Neem-On extract is less toxic to Indian major carps Labeo rohit, than other synthetic insecticides used in fish-farming (Bhat et al, 2012). The acute toxicity values of several Neem preparations and some for pure azadirachtin for laboratory animals and some non-target species have been studied extensively (Patil et al, 2011;Saravanan et al, 2011;Salman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%